An efficient in situ monitoring strategy for an active aquatic surface omni-directional sensing device. (18th July 2022) - Fujii, Yasuyuki; Tuan Tran, Dinh; Lee, Joo-Ho
Abstract : The monitoring applications employed for the identification and analysis of environmental changes in aquatic areas such as lakes and seas have gained interest in recent years. The conventional monitoring methods are based on manual labor, which presents high financial/temporal costs along with physical risks. Autonomous robots and low-cost sensing devices have been proposed in recent years as alternatives to the conventional methods. This study presents a novel sensing device which automatically moves to an arbitrary position or maintains a fixed position in the water for long-term environmental monitoring. The proposed device presents a portable design, low manufacturing cost, omni-directional mobility, and sustainable operation. It was observed in our previous study that an efficient mobility strategy is required for the long-term operation of sensing devices. In this study, position keeping strategies are developed assuming that the sensing device employs in situ water quality monitoring; these strategies are in the simulation environment and the real field to determine the most efficient one. In the future works, traveling experiments with multiple observation points will be conducted for monitoring larger area. GRAPHICAL ABSTRACT: UF0001